2003
DOI: 10.1046/j.1524-4725.2003.29050.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging, Treatment, and Microscopic Confirmation of Clearance of Basal Cell Carcinoma

Abstract: The ability to use CM to image in real time without discomfort to the patient makes it a powerful tool to assist in the diagnosis of skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Its mode of action implies the induction of the innate immunity resulting in a selective antitumoral immune response through the activation of dendritic cells, cytotoxic T lymphocytes and proinflammatory cytokines. RCM has been used for monitoring and evaluation of treatment efficacy of basal cell carcinoma and lentigo maligna melanoma during topical IMIQ therapy [36,37,38]. To our knowledge, no systematic RCM evaluation of treatment response of AK to IMIQ has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Its mode of action implies the induction of the innate immunity resulting in a selective antitumoral immune response through the activation of dendritic cells, cytotoxic T lymphocytes and proinflammatory cytokines. RCM has been used for monitoring and evaluation of treatment efficacy of basal cell carcinoma and lentigo maligna melanoma during topical IMIQ therapy [36,37,38]. To our knowledge, no systematic RCM evaluation of treatment response of AK to IMIQ has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the confocal features correlate well with the stained section of a biopsy. Furthermore, BCC-patients were treated with a topical immune response modifier; the presence, as well as the clearance of the BCC was analyzed by reflectance microscopic measurements [40,41]. Another study looks at the ability for accurate differentiation of actinic keratoses (AK) vs. SCC, reaching the conclusion that the reflectance LSM is currently restricted because of the limited depth visualization [42].…”
Section: Application Of Laser Scanning Microscopy In Diagnoses and Thmentioning
confidence: 99%
“…2 If there is clinical evidence of persistent tumor at this assessment, a biopsy or other alternative intervention should be considered. 2 Case reports, open-label, and phases II and III clinical trials have demonstrated the efficacy and safety of imiquimod in the treatment of sBCC (Table II) [37][38][39][40][41][42][43][44][45] with cure rates ranging from 43% to 100%. 37-39-43-45 Complete response has been reported in as little as 6 weeks but may take as long as 18 weeks [42][43] (Table II).…”
Section: Supercial Basal Cell Carcinoma (Sbcc)mentioning
confidence: 99%